Efficiency Control Improvement Of Diesel Engines Conditions By Using The Method Of Analytical Synchronization Of Monitored Data - Zalozh, Vitalii; Tarasenko, T; Varbanets, R (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Improving the efficiency of the ship's diesel power plant is becoming increasingly important every year. This is primarily due to the restrictions on emissions of sulfur and nitrogen oxides into the atmosphere during the operation of the ship's diesel engines. Article is devoted to the problem of synchronization of data monitoring working process in transport diesel engines operation. The accuracy of data synchronization determines the error in determining power, control of the main engine systems operation and its diagnostics. The method of solving the synchronization problem must be analytical. The method of solving the synchronization problem must be analytical. In comparison the hardware methods used in most diagnostic systems of the working process of diesel engines have several disadvantages. It is impossible to conduct rapid diagnostic control in operation, non-stationary phase and amplitude errors in calculation the main parameters of the working process, the need for preparatory operations and related need for temporary withdrawal of diesel engine operation, complexity and high cost of diagnostic control. An analytical synchronization method is developed based on the top dead center coordinate determination algorithm, which uses three stages: linear, sinusoidal and model equal to zero the first derivative of the pressure under compression. The proposed method of analytical synchronization gives the obvious advantages for monitoring working process systems of diesel engines. The error in determining the main parameters of the working process and the indicator power does not exceed 2.5%.